Security of Supply in Electricity Markets - Sebastian Schwenen (Copenhagen Business School (CBS), 2011)
The regulatory approach to supply security in electricity markets has been substantially altered since power markets were partly privatized and reregulated in the mid 1990's, when regulators chose to rely on market based prices and decentralized commercially based decisions on generation capacities. Prior to this market restructuring power systems basically worked as planned economies, however, the decentralization of production decisions introduced stochastic elements to electricity systems. Additionally, since the early 2000's, power generating companies, often incentivized by the state, started increasing the share of renewable but intermittent energy sources in their generation portfolios. Due to its intermittency the production process of wind, solar and hydro power is difficult to plan and therefore the final amount of power that enters the market at each point in time becomes difficult to predict. As the level of power supply intermittency increases, so also do the number of challenges that market based approaches face in organizing secure power systems....
hdl:10398/8376
Keywords: 650